Barriers to cataract surgery in Africa: a systematic review - Aboobaker, Shaheer (Division of Ophthalmology, 2016)
Background: Cataract remains the leading cause of blindness in Africa. We sought to review the available literature relating to barriers to cataract surgery in Africa. Methods: A review of the literature was undertaken using PubMed and Google Scholar using the search terms "barriers, cataract, Africa, cataract surgery, cataract surgical coverage (CSC), and Rapid Assessment of Avoidable Blindness (RAAB)". The review covered the period 1999-2014. Results: In RAABs, barriers related to awareness and access were more commonly reported than acceptance, while non -RAAB studies reported cost as the most commonly reported barrier. The few qualitative studies tended to report community and family dynamics with regard to barriers to cataract surgery. CSC was reported as lower in females in 88.2% of the studies. Conclusion: Studies of barriers to cataract surgery give variable responses. This may be due to the study context but also may be due to the type of data collection. It is likely that qualitative data will give a deeper understanding of the complex social, family, community, financial and gender issues relating to barriers to uptake of cataract surgery in Africa.